DETECTION OF MYCOPLASMA CAPRICOLUM SUBSP. CAPRIPNEUMONIAE AND MANNHEIMIA HAEMOLYTICA AS CAUSATIVE AGENTS OF PLEUROPNEUMONIA IN GOATS - Fatemeh Namazi (Asociación Colombiana de Infectología, 2020)
Objective: The aim of the study was detection of two major causative agents of pleuropneumonia, Mycoplasma capricolum subsp. capripneumoniae (Mccp) and Mannheimia haemolytica, in goats. To the best of our knowledge, this study is the first investigation of Mccp in Iran. Methods: 50 grossly suspected lungs to pleuropneumonia and 10 healthy samples were collected from Shiraz abattoir. Results: Histopathological evaluation of tissue samples showed various diagnosed pneumonias including 40% bronchointerstitial pneumonia (20 samples), 34% interstitial pneumonia (17 samples), 10% fibrinopurulent bronchopneumonia (5 samples), 12% purulent bronchopneumonia (6 samples) and 4% chronic pneumonia (2 samples). In molecular study, all 50 suspected samples and 10 healthy ones by PCR showed no Mccp positive sample, but the detection rate of M. haemolytica in suspected samples was 14% and in healthy lungs was zero. Conclusions: It may be concluded that goats referred to Shiraz abattoir is free of Mccp. Further sampling and molecular testing at the level of suspected herds to CCPP can be useful.